Revisiting the Indonesian prefixes peN-, pe2- and per- - Denistia, Karlina (Masyarakat Linguistik Indonesia, 2018)
This paper presents a literature review on three nominalising prefixes in Indonesian: peN-, pe2- and per- whose function is to create agent, instrument, or patient (e.g. tulis ‘to write’ – penulis ‘writer’, wisata ‘travel’ – pewisata ‘traveller’ and tapa ‘ascetic’ – pertapa ‘hermit’). The ‘N-‘ in peN- stands for ‘nasal’ due to its five nasalised allomorphs (e.g. pen-, peny-, pem-, peng-, and penge-). However, there is one peN- allomorph which is not nasalised, henceforth called pe1-. Pe2-, the other prefix, is described as having similar in form and meaning as pe1-. Per-, the last prefixed is described as the archaic nominalisation prefix. Some theorists believed that Indonesian nominalisation is derived from peN- and per- in which pe2- belongs to per-, some argued that it is formed from peN- in which pe2- is one of peN- variant or per-, and some stated that nouns are derived from peN-, pe2- or per-. PeN- is described as the most productive of the three prefixes and is believed to correlate with the verbal prefix meN- (e.g. menulis ‘to write’ – penulis ‘writer’) with the process of affix substitution. Whereas pe2- is described as corresponding with the verbal prefix ber- (e.g. berwisata ‘to travel’ – pewisata ‘traveller’). Thus far, there has been no consensus addressing whether pe2- the allomorph of peN- or per- or none of them. This paper will examine existing theories and research relevant to this issue.